Strategi promosi dalam pengembangan Perpustakaan Pascasarjana UIN Imam Bonjol Padang - Eviendrita, Eviendrita (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Library is one of the important elements in higher education institutions. The Postgraduate Library of UIN Imam Bonjol is an integral part of the higher education system that aims to support research and development of knowledge. This library needs an effective promotional strategy to increase the use and utilization of collections and services available. This study aims to analyze the promotional strategies that have been implemented by the Postgraduate Library of UIN Imam Bonjol in an effort to develop and increase the use of its services. The research method used is descriptive qualitative method by collecting data through observation, interviews, and documentation. The results showed that the Postgraduate Library of UIN Imam Bonjol has implemented various promotional strategies, including book fairs, workshops, social media, and collaboration with study programs and other institutions on campus. These strategies aim to increase user awareness about the collections available, the services provided, and the importance of the library in supporting academic and research activities. There are still some challenges such as budget and human resource limitations that affect the effectiveness of the implementation of these promotional strategies. This research contributes to the importance of promotional strategies in the development of UIN IB postgraduate library.